Advances in Vision Research, Volume I : Genetic Eye Research in Asia and the Pacific - Prakash, Gyan; Iwata, Takeshi (Essentials in Ophthalmology, 2017)
This book presents the state of the art in genetic eye research in Asia and the Pacific. Though there has been an explosion of information on genetic eye research in western countries, more than sixty percent of the human genes involved in eye diseases in the Asian and Pacific population remain unknown. However, new efforts and a new awareness have sparked important discussions on the subject, and new plans are being implemented to discover the genes responsible for many eye diseases in the population. The book reviews the latest findings; its content ranges from genetic aspects of human migration to DNA sequence analysis, genome-wide association analysis, and disease phenotypes. The efforts of the Asian Eye Genetic Consortium (AEGC) are also discussed. The book's editors have been instrumental in developing strategies for discovering the new Asian genes involved in many eye diseases. All chapters were written by leading researchers working on Asian eye genetics from the fields of Human Genetics, Ophthalmology, Molecular Biology, Biochemistry, Sensory Sciences, and Clinical Research. Advances in Vision Research, Volume I will prove to be a major resource for all researchers, clinicians, clinical researchers, and allied eye health professionals with an interest in eye diseases among the Asian population.